ARCHWAy: an innovative educational program advancing the public health workforce - Beth Ann Swan; Quyen Phan; Kevin Crawford; Sarah Febres-Cordero; Lalita Kaligotla; Roxana Chicas; Nicholas A. Giordano; Susan Brasher; Rebekah Chance-Revels; Anne Spaulding; Laika Steiger (BMC, 2024)
Abstract Background Community health workers (CHWs) are vital yet often invisible contributors to care coordination, health equity, and public health (PH) in medically underserved areas. The Atlanta Regional Community Health Workforce Advancement (ARCHWAy) Program leverages cross-sector partners to increase the number of CHWs on integrated care teams in metro Atlanta in the United States. Methods The ARCHWAy Program provides an innovative educational curriculum guided by United States Department of Labor CHW competencies and cross-walked with the Georgia CHW Initiative competencies. The 12-week in-person/online curriculum includes 155 h of content on becoming a CHW, mental health first aid, social determinants of health, trauma informed care, population health, community outreach, engagement, and capacity building, resiliency, communication, care coordination, advocacy, emergency preparedness, health promotion/disease prevention, 20 h of simulation including motivational interviewing, point of care testing, first aid, and 80 h of experiential learning through field placements. Project team members represent racial, ethnic, linguistic, and gender diversity ensuring culturally congruent content. Results Since program inception, the public health workforce in the region has been expanded by over 200 CHWs to date (goal of 446 CHWs) with specialized training offered in both English and Spanish. Discussion Positioning well-trained CHWs as members of integrated care teams promotes health equity by advancing PH, strengthening the PH workforce, reducing health disparities, and helping underserved populations address social determinants that can undermine health. The ARCHWAy program, by increasing CHW employment readiness through developing field placements with cross-sector partners, aspires to set the standard for apprenticeships in CHW training programs.